Effectiveness of problem-based learning model in empowering creative thinking ability of elementary school students - Rasimin Rasimin; Sukron Ma'mun (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2021)
This study aimed at determining the effectiveness of the Problem Based Learning (PBL) model in empowering the creative thinking skills of elementary school students in Pagergunung Ulujami Pemalang in social studies (IPS) learning. The research population was all fifth graders of the elementary school in Pagergunung Ulujami, Pemalang Regency, the sample of this study was taken using quasi-experimental, while data collection technique used pre-test and post-test techniques on students' creative thinking abilities. Meanwhile, the statistical test analysis technique used the proportion test and the difference between the two proportions. The results showed a significance level of 5%. The conclusions of the study are: (1) PBL model is effective in the aspect of students' creative thinking abilities, but less effective in the aspect of problem-solving abilities in IPS learning, (2) PBL model is more effective than conventional learning in both students' creative thinking and problem-solving ability.